2019
DOI: 10.1002/app.47663
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐treated Bentonite as filler in the development of novel composite PVA hydrogels

Abstract: In this study, novel eco‐friendly hydrogel adsorbents were synthesized based on poly(vinyl alcohol) (PVA) and different contents of an acid‐treated bentonite (1–5 wt %). The hydrogels were prepared by freezing–thawing, which is a simple and nontoxic method. The materials were morphologically and thermally characterized by means of swelling assays, X‐ray diffraction, scanning electron microscopy, dynamic scanning calorimetry, and thermogravimetric analysis in order to evaluate the effect of acid‐treated bentoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 58 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…As Zhou and collaborators have previously reported for similar magnetic systems, the cross‐linking dots are produced as a result of the strong hydrogen bonding interactions between the MNPs and the –OH groups from the PVA 87 . This kind of entanglement involving hydrogen bonding interactions between the PVA matrix and the included filler to form the desired composite material is a well‐known fact 32 …”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…As Zhou and collaborators have previously reported for similar magnetic systems, the cross‐linking dots are produced as a result of the strong hydrogen bonding interactions between the MNPs and the –OH groups from the PVA 87 . This kind of entanglement involving hydrogen bonding interactions between the PVA matrix and the included filler to form the desired composite material is a well‐known fact 32 …”
Section: Resultsmentioning
confidence: 83%
“…87 This kind of entanglement involving hydrogen bonding interactions between the PVA matrix and the included filler to form the desired composite material is a well-known fact. 32 In accordance to the obtained results it was decided to continue the research only considering four of the developed materials: the hydrated and the dried, high-FeOx beads. The magnetization studies revealed that there is no significant difference between the saturation magnetization (Ms) of the C0 and C3 samples ( Figure 11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… χ% =ΔHΔH°×WPVA ×100 where ΔH was calculated as the area under the melting peak, ΔH° is the heat needed to melt a 100% crystalline PVA (138.6 J g −1 ), and W PVA is weight fraction of the PVA polymer in the hydrogel sample with respect to deionized water. [ 50,89,90 ] Figure 7b provides a view of the trend of crystallinity degree with increasing starch.…”
Section: Introduction Of Synthetic Hydrogelsmentioning
confidence: 99%